Technique, langue, traduction. Il y a sertissage et sertissage - Lerat, Pierre (HERMES - Journal of Language and Communication in Business, 2016)
Little theoretical research has been published on LSP. The most useful approach is that of the ‘whole language’ applied to specialised discourse, an approach which only seems to be represented by Benveniste and Harris. How can a French predicative word such as sertissage be applied in a non-lexicographical approach ? It is suggested to compare the uses of this word in French and its conditional equivalents in other languages (de., en., es., it.), thereby bringing out a conflict between the ‘cultural stereotype’ and the ‘technical stereotype’, and also between national culture and international culture.